Pedestrian facilities for elderly people at UTC area, Kuantan - Siti Nor Suraya, Zulaini (2017)
Pedestrian facilities are crucial to create a comfortable environment and unrestricted facilities, especially among elderly. This paper study places particular emphasis on accessibility in urban areas within the city center. The objective of this study is to identify the needs of the elderly on the pedestrian facilities. In addition, determining the barriers existing in urban areas to be a factor of elderly people is not safe to use. Finally, proposed a framework to facilitate pedestrian facilities to facilitate all inclusive people can use them well. The findings show that most of respondents were unsatisfied with the level of comfort particularly in terms of pedestrian facilities provided. In contrast, field observations revealed that the city center had poor maintenance of facilities reflected in improper condition of walkways and street furniture such as benches.